Tetrabenazine versus deutetrabenazine for Huntington's disease : twins or distant cousins? - Rodrigues, Filipe Brogueira (2017)
© 2017 The Authors. Movement Disorders Clinical Practice published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.